Effects of antioxidants extracted from leaves of “banaba” (Lagerstroema speciosa L.) mangosteen (Garcinia mangostana L.) and “Tsaang gubat” (Ehretia microphylla L.) on the oxidation stability of biodiesel from Jatropha curcas L - Demafelis, Rex B. (The Philippine Journal of Crop Science, 2012)
The effects of the antioxidant extract from “banaba” (Lagerstroemia speciosa L.), mangoesteen (Garcinia mangostana L.) and “tsaang gubat” (Ehretia microphylla L.) on the oxidation stability of biodiesel from Jatropha curcas L. were determined based on the Induction Period (IP) of the samples using the Rancimat method of oil stability index. The most appropriate extraction time was found to be 6 h for “banaba” and 12 h for both mangosteen and “tsaang gubat”. The data obtained for the “banaba”, mangoesteen and “tsaang gubat” extracts had a regression coefficient (R2) of 0.69, 0.80 and 0.89, respectively, which statistically indicated a linear positive correlation between the loading rate (ppm extracts) and the induction period (h). The antioxidant derived from mangosteen leaves proved to be the most effective and economical compared to the other natural antioxidants, and a commercial antioxidant (Baynox Plus). At the lowest loading rate of 2604 ppm of mangosteen extract, the induction period was 17.52, greatly exceeding all the three standards: the American/ASTM D6751 (3-H IP), European/EN 14214 (6-h IP) and Japanese/JASO M360 (10-h IP). Results of this study showed that the mangosteen extract may be used to improve the stability of biodiesel significantly.